Effects of using conventional assistive devices on spatiotemporal gait parameters of adults with neurological disorders: A systematic review protocol - Jordana de Paula Magalhães; Sheridan Ayessa Ferreira de Brito; Merrill Landers; Aline Alvim Scianni; Poliana do Amaral Yamaguchi Benfica; Carolina Luisa de Almeida Soares; Christina Danielli Coelho de Morais Faria (PLoS ONE, 2025)
Individuals with neurological disorders often experience gait impairments that contribute to increased disability, long-term care risk, and higher healthcare costs. The prescription of assistive devices is a commonly employed strategy to compensate for gait impairments in this population. Despite being recommended by various guidelines, there are limited recommendations for prescribing these devices. Furthermore, the effects of using assistive devices on the gait of individuals with neurological disorders are poorly known. Therefore, the aim of this systematic review is to investigate the immediate, short, and long-term effects of using conventional assistive devices (e.g., canes, crutches, walkers) on gait parameters of adults with neurological disorders. This Systematic review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42024542695) and was conducted following Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). Experimental studies that investigated the effects of using conventional assistive devices on the gait of individuals with neurological disorders will be included. Electronic searches will be conducted in Medical Literature Analysis and Retrieval System Online (MEDLINE Ovid), Excerpta Medica Database (Embase Classic +  Embase Ovid), Physiotherapy Evidence Database (PEDro), Scientific Electronic Library Online (Scielo), Cumulative Index to Nursing and Allied Health Literature (CINAHL Database), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) and gray literature. The reference lists of the included studies will be manually searched. Two trained independent reviewers will select the studies, extract the data, and assess the methodological quality of the included studies using the Cochrane Risk of Bias tools. Disagreements between reviewers will be solved through consensus or by a third independent reviewer. The quality of the evidence will be assessed (GRADE). If a sufficient number of comparable studies are available, subgroup analysis will be conducted and we will consider doing a meta-analysis if the studies are homogeneous. The review will be reported following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA 2020 statement). The results of this review will provide useful information about the effects of assistive devices on gait in different neurological disorders comprehensively and systematically. Investigating the immediate, short and long-term effects may generate useful information for making clinical decisions related to the training time for using these devices. If a meta-analysis is possible, the prescription of these devices could be improved based on knowledge of their effects. Finally, the results of this systematic review will identify gaps in the literature and guide future research.